Debord, Time and Spectacle : Hegelian Marxism and Situationist Theory. - Bunyard, Tom (Historical Materialism Book Ser., 2017)
In Debord, Time and Spectacle Tom Bunyard provides a detailed philosophical study of the theoretical work of Guy Debord and the Situationist International. Drawing on evidence from Debord's books, films, letters and notes, Bunyard reconstructs the Hegelian and Marxian ideas that support Debord's central concept of 'spectacle'. This affords a reconsideration of Debord's theoretical claims, and a reinterpretation of his broader work that foregrounds his concerns with history and lived time. By bringing Situationist theory into dialogue with recent reinterpretations of Marx, this book also identifies problems in Debord's critique of capitalism. It argues, however, that the conceptions of temporality and spectacle that support that critique amount to a philosophy of praxis that remains relevant today.